Digital Investment Behavior of Muslim Investors in Cryptocurrency Platforms in Indonesia - Hartono, Hartono; Indah, Nopiani (Journal of Social Commerce, 2025)
Behavior regarding cryptocurrency investment among Muslim users cannot be interpreted in a technology-oriented or psychologically-focused manner. It reveals the limitations of the existing behavioral frameworks that leave out the moral examination, social responsibility, and symbolic integrity that comes with an ethical decision during digitally mediated financial environment. The present research thus deposes an assumption that self-efficacy, anxiety, and habit are only neutral predictors. By means of structural equation modeling of the data that was collected among 246 Muslim investors, the present research results confirm that intention is not an original as well as arbitrarily assigned form, but one that is developed by being in line with moral obligation and social recognition. The concept doctrinaire of self-efficacy should be geared up only on the basis of being confident rather it should be regarded as authorized agency. Anxiety, instead of having impeding effects on behavior, acts as a filter of legitimacy where clarity is not settled theologically. Besides, the insignificance of habit is not a sign of the lack of behavior; it is a product of constant moral bargaining. These findings encourage a redefinition of the nature in which digital behavior of investing is theorized. Muslim investors do not find themselves in these platforms as passive beings but as moral agents who are unwilling to allow the automation of financial activities to occur without prior consent. Therefore, the behavioral science needs to correct its oversight of interpretive acumen and stratum of righteousness that orient action in the religious scenario of finance.